Morpholocial and functional recovery of brain associated with sobriety from alcoholism - Burhanoğlu, Sabri; Hızlı Sayar, Gökben (Journal of Dependence, 2014)
Objective: Alcoholism results in grey and white matter brain injury, which is accompanied by cerebral volume loss and neuropsychological impairments. Cerebral volume loss, metabolic and neuropsychological impairments associated with alcohol addiction may be in part reversible, even during early stages of sobriety. Method: In this review we discuss the morphological and functional recovery of brain in sobriety after alcohol addiction. The studies about this subject are overviewed. Results: Sobriety after alcohol addiction results in brain cell genesis, increased cholin levels, increased volume ofgray and white matter, reorganisation of brain circuits and decrease in ventricular volume that could contribute to the return of executive functions, better memory, attention, behavioral control and mood. Previous studies suggested that regular physical exercise in sobriety period may lead to increase in rate of neurogenesis. Alcohol consumption in moderate amounts in legal limits or as social drinking also reported to have profound negative effects on neurogenesis. This result illustrates the importance of sobriety for the patients with damaged brain functions. Conclusion: Further understanding the mechanisms of neuronal recovery in sobriety may serve as a valuable model of brain regeneration and, would become relevant for treatment of other neurodegenerative disorders.